ADAPTASI MASAKAN JEPANG DI INDONESIA PADA RESTORAN FRANCHISE MARUGAME UDON DAN HAKATA IKKOUSHA DI BALI - Siti Ayu Ningsih; Ni Luh Gede Meilantari; Betty Aritonang (Program Studi Sastra Jepang Fakultas Bahasa Asing Unmas Denpasar, 2021)
This research discusses the intercultural adaptation of Indonesia and Japan by Marugame Udon and Hakata Ikkousha restaurants in Indonesia, especially in Bali. This research uses the theory of Intercultural Adaptation (an Integrative Communication Theory) proposed by Young Yun Kim. Sources of data used in this research are interviews and questionnaires. The analysis in this research was carried out by using qualitative descriptive methods and using informal methods in presenting the data analysis. Based on the research results, it can be seen that differences in culture, religion, environment and people's tastes determine the acceptability of Japanese food in Indonesia. The majority of Indonesia's population is Muslim, therefore halal food an important thing in Indonesia. Marugame Udon and Hakata Ikkousha restaurants adapt to the surrounding environment by adjusting ingredients and spices and cutlery according to the tastes of the Indonesian people. The adaptation process made several menu differences between Marugame Seimen and Hakata Ikkousha restaurants in Japan and Marugame Udon and Hakata Ikkousha restaurants in Indonesia.